2009
DOI: 10.1177/0022034509339487
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry Proanthocyanidins Inhibit MMP Production and Activity

Abstract: Matrix metalloproteinases (MMPs) produced by resident and inflammatory cells in response to periodontopathogens play a major role in periodontal tissue destruction. Our aim was to investigate the effects of A-type cranberry proanthocyanidins (AC-PACs) on: (i) the production of various MMPs by human monocyte-derived macrophages stimulated with Aggregatibacter actinomycetemcomitans lipopolysaccharide (LPS), and (ii) the catalytic activity of recombinant MMP-1 and MMP-9. The effects of AC-PACs on the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 36 publications
4
64
0
4
Order By: Relevance
“…In the present study, we showed that AC-PACs inhibited collagen degradation by P. gingivalis in a dose-dependent manner, suggesting that ACPACs may contribute to reducing the destructive process. Interestingly, we previously showed that AC-PACs have the ability to inhibit the activity of recombinant human matrix metalloproteinases (MMP-1 and MMP-9) and the secretion of various MMPs by macrophages (29). Using a reconstituted basement membrane model composed of laminin, type IV collagen, proteoglycans, and entactin, we also showed that AC-PACs could inhibit the invasiveness of P. gingivalis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present study, we showed that AC-PACs inhibited collagen degradation by P. gingivalis in a dose-dependent manner, suggesting that ACPACs may contribute to reducing the destructive process. Interestingly, we previously showed that AC-PACs have the ability to inhibit the activity of recombinant human matrix metalloproteinases (MMP-1 and MMP-9) and the secretion of various MMPs by macrophages (29). Using a reconstituted basement membrane model composed of laminin, type IV collagen, proteoglycans, and entactin, we also showed that AC-PACs could inhibit the invasiveness of P. gingivalis.…”
Section: Discussionmentioning
confidence: 84%
“…To investigate the effect of AC-PACs on various pathogenic properties of P. gingivalis, up to 100 g/ml of AC-PACs was used, since this concentration has been reported to be nontoxic for human cells (29). Biofilm formation by P. gingivalis was significantly decreased by 50 and 100 g/ml AC-PACs.…”
Section: Resultsmentioning
confidence: 99%
“…A utilização de PAs visando à inibição de proteases tem sido investigada não somente buscando a estabilidade da união resina-dentina, mas também para a prevenção e a redução de câncer 20 , e controle da progressão de doenças periodontais 15,21 . As MMPs são proteases zinco/cálcio dependentes que necessitam de íons cálcio para manter sua estrutura terciária, bem como de íons zinco para catalisar o processo de hidrólise.…”
Section: Discussionunclassified
“…A prolina aumenta a especificidade da interação com as PAs, favorecendo a formação de ligações de hidrogênio entre a carbonila da amida proteica com a hidroxila fenólica 14 . Além disso, tem sido demonstrado que as PAs também desempenham um papel importante tanto na inibição da produção das MMPs -1, -3, -7, -8, -9 e -13 liberadas pelos macrófagos quanto na atividade catalítica das MMPs -1 e -9 15,16 . Estudos anteriores têm relatado que a aplicação de PA (extraída de semente de uva) na dentina desmineralizada apresenta resultados significativos tanto nas propriedades mecânicas como na resistência de união da interface adesiva após 10 e 60 minutos de tratamento.…”
Section: Introductionunclassified
“…In addition to create covalent cross-links in collagen, cross-linkers are capable to cross-link the protease enzymes directly and interfere with their molecular mobility 65) . The other supposed paradigm is that PA may indirectly interfere with production and activation process of proteases by modulating host immune responses 74) . There are some reports about PA MMP inhibitory effects somewhere in human body aside from dentin, as the case of point, cranberry PA can inhibit production and secretion of MMP-1 and MMP-9 by macrophages in response to periodontal pathogens 75) .…”
Section: Pa-dentinal Matrix Metalloproteinase Interactionsmentioning
confidence: 99%